Caudal Duplication Of Hind Gut And Lower Genitourinary Tract In A Female Child - Dr. V.N.S. Yadava; Dr. Jina Raghwendra Prasad; Dr. Kushwaha Komal Prasad (Indian Journal of Plastic Surgery)
Two year old, with congenital anomaly of duplication of hind gut upto sigmoid flexor with one open end and other closed, as well as double bladder and double urethra opening below two clitoris and two vaginal vaults is presented.